Development and evaluation of vinpocetine inclusion complex for brain targeting - Jiaojiao Ding; Jinfeng Li; Shirui Mao (Elsevier, 2015)
The objective of this paper is to prepare vinpocetine (VIN) inclusion complex and evaluate its brain targeting effect after intranasal administration. In the present study, VIN inclusion complex was prepared in order to increase its solubility. Stability constant (Kc) was used for host selection. Factors influencing properties of the inclusion complex was investigated. Formation of the inclusion complex was identified by solubility study and DSC analysis. The brain targeting effect of the complex after intranasal administration was studied in rats. It was demonstrated that properties of the inclusion complex was mainly influenced by cyclodextrin type, organic acids type, system pH and host/guest molar ratio. Multiple component complexes can be formed by the addition of citric acid, with solubility improved for more than 23 times. Furthermore, In vivo study revealed that after intranasal administration, the absolute bioavailability of vinpocetine inclusion complex was 88%. Compared with intravenous injection, significant brain targeting effect was achieved after intranasal delivery, with brain targeting index 1.67. In conclusion, by intranasal administration of VIN inclusion complex, a fast onset of action and good brain targeting effect can be achieved. Intranasal route is a promising approach for the treatment of CNS diseases.